SELF-ORGANİZATİON İN TERMS OF CLASSROOM MANAGEMENT OF PHYSİCAL EDUCATİON TEACHERS İN SCHOOLS İN MİSAN GOVERNORATE - Azhar Abdulwahab Mohammed (American Journals Publishing, 2023)
The aim of the research is to identify the relationship between self-organization in terms of classroom management of physical education teachers, and the researcher used the descriptive approach in the survey method and correlational relationships, and the researcher identified the research sample, which was represented by physical education teachers numbering (178), they were distributed to three samples, exploratory sample (8) school, and preparation sample (85), and application sample (85) school, and the researcher followed all scientific procedures in preparing the study scales, Which resulted in a measure of self-organization in its final form, as it contained (34) paragraph, and the scale of classroom management (30) paragraph, where the researcher applied the standards to the study sample, and after collecting data and processing it statistically, the researcher came out with several conclusions that physical education teachers have a good level of self-organization in terms of classroom management, and recommended maintaining this level and establishing courses in classroom management, organizational and educational sciences